P096 Synovial tissue remodelling as a means of tissue memory. (21st February 2018) - Olmos Calvo, I; Byrne, RA; Bonelli, M; Niederreiter, B; Alasti, F; Karonitsch, T; Holinka, J; Steiner, G; Smolen, JS; Ertl, P; Kiener, HP
Abstract : Introduction: The synovium demonstrates a distinct cellular structure with a densely packed synovial lining layer that sits on top of a loosely organised sublining layer. In rheumatoid arthritis (RA), this tissue hosts the inflammatory reaction and undergoes drastic structural changes. We hypothesise that this inflammatory remodelling results in tissue dysfunction, thereby perpetuating the inflammatory process. To explore the relationship between tissue structure and function, we use a 3D human synovial organoid culture system to model healthy and diseased synovium. Methods: FLS from RA patients were resuspended in Matrigel and cultured as 3D organoids for an extended period of time. This allows FLS to re-establish a synovial tissue-like structure. To mimic inflammation, 3D synovial organoids were challenged with TNF. A re-stimulation experiment was designed in which synovial organoids were exposed to TNF for 10 days, followed by a 3 day wash out phase. Thereafter, the organoids were re-stimulated with TNF. To prevent TNF-driven remodelling, Marimastat, a broad MMP inhibitor, was added during the first TNF stimulation. For selected experiments, synovial tissue-like structure was assessed by HE staining in paraffin embedded sections of synovial organoids. qPCR and RNA Seq were used in gene expression profiling. IL-6, IL-8 and MMP3 protein production was determined by ELISA. Results: TNF-stimulated synovial organoids demonstrated lining layer hyperplasia and cellular condensation in the sublining layer. After TNF-stimulation, gene expression of MMP1, MMP3 and IL-6 and protein production of IL-6, IL-8 and MMP3 was upregulated. Upon re-stimulation of synovial organoids with TNF, protein levels of IL-6, IL-8 and MMP3 were significantly increased when compared to previous stimulations. In order to explore whether this effect is due to TNF-induced structural changes, tissue remodelling was blocked using Marimastat. IL-6 protein level was reduced in 21%. To further explore the increased TNF response upon re-stimulation, epigenetic mechanisms are currently being tested. Conclusions: TNF stimulation has a direct effetc in synovial organoids function and structure. TNF-driven tissue remodelling is associated with an increased in IL-6, IL-8 and MMP3 expression response upon re-stimulation. Inhibition of TNF-induced remodelling partially prevents this effect. Additional epigenetic mechanisms may account for tissue memory. Disclosure of interest: None declared